Analysis of Government Administration Systems in Indonesia, Malaysia, Vietnam - Adela Magdalena Jonathan Marramis; Sri Roekminiati; Zainal Fatah; Dendy Homeland Wirawan (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research analyzes the administrative systems in Indonesia, Malaysia, and Vietnam, focusing on decentralization, regional autonomy, good governance, public service, accountability, transparency, efficiency, and effectiveness. These three countries have different approaches to managing public administration, influenced by their respective political systems, history, and socio-economic conditions. In Indonesia, decentralization and regional autonomy are prominent because of the strengthening of the role of local governments, although challenges in terms of accountability and coordination between levels of government still exist. With its federal system, Malaysia shows a high efficiency level in administration but faces issues of transparency and public participation. Meanwhile, Vietnam, as a socialist country, centralized administration in the central government, but started to reform to improve efficiency and accountability. This study found that the success of public administration reforms in the three countries depends on applying good governance principles, including strengthening accountability, transparency, and efficiency of the administrative system. The study makes an important contribution to developing public administration systems in developing countries to achieve effective governance that is responsive to the needs of the people. Although the three countries have made progress in some sectors, the main challenges still revolve around improving transparency, strengthening accountability, and managing resources efficiently